Модель поражения цели с заданной вероятностью автоматической пушкой 2А42 - Анипко, О. Б.; Рикунов, О. М. (НТУ "ХПИ", 2007)
The questions by definition of the maximal deviations on range and on direction are considered. The basic technical requirements for maintenance effective of impact in the target from the automatic gun 2А42.
Keywords: отклонения дальности; отклонения направления; эффективность попадания